Transformasi Mahar Perkawinan Melalui Estetika di Desa Paberasan Kabupaten Sumenep - Khoirin Nisa'; Darmawan Darmawan (AL-HUKAMA': The Indonesian Journal of Islamic Family Law, 2021)
One of the essential parts of marriage is the dowry that must be given from the prospective husband to the future wife. Dowry is not included in the pillars of marriage but needs to be delivered to respect the existence of women. This study aims to determine whether the dowry with an aesthetic concept can be affordable? To what extent is the aesthetic limit in the dowry? The research method used in this study is a mixture of library research and field research. In addition to using literature such as books, notes, and several previous studies, this study also collected data through interviews. Giving dowry by carrying out the aesthetic concept, namely using the date of marriage, no prohibition is found. As long as the dowry is affordable and the husband can give it, then it may be done, of course, with due observance, that the dowry does not conflict with the Shari'a. In aesthetics, there are five values, as described by Laurie Schneider Adams, namely: material values, intrinsic values, religious values, nationalism values, and psychological values. The most dominating value in this study is the psychological value because it can bring a reaction of happiness and pleasure to the subject. In the view of psychology, happiness can be created by oneself, and everyone has their parameters for creating happiness for themselves. Aesthetics in this dowry can give value and satisfaction to the subject because it contains beauty.